Quasi‐elliptical band‐pass filters based on compact spiral resonators for C‐band applications. Issue 8 (27th February 2019) - Cidronali, Alessandro; Collodi, Giovanni; Maddio, Stefano; Pelosi, Giuseppe; Selleri, Stefano
Abstract: This letter proposes a quasi‐elliptical passband filter in via‐less microstrip technology. The filter is based on the Archimedean spiral, enabling a compact and low‐loss response with sharp transitions to stop bands. The developed filters fabricated on a commercial substrate, present losses below 2 dB within a 3 dB bandwidth of 500 MHz, and isolation exceeding 20 dB. Its extremely compact dimension, about 0.018   λ 0 2, and the low‐cost of fabrication, permits the integration within compact front‐end PCB.